Bilateral Venous Infarcts Secondary To Thrombosis: Two Cases - (:unkn) unknown (JOURNAL NEUROLOGICAL SCIENCES, 2009)
Objective: To present two cases with deep-seated bilateral venous infarcts. Case 1: An 18-year-old woman was admitted to the hospital with a state of akinetic mutism, bilateral papiledema and a left-sided hemiparesis (MRC grade 2). Her medical history disclosed multiple attacks of diarrhea during the previous week. Brain MRI showed bilateral, symmetrical thalamic lesions compatible with deep-seated venous infarcts. Brain MR venography revealed a lack of signal at the level of the left lateral and straight sinuses. Laboratory evaluation showed protein C deficiency and heterozygote factor V Leiden mutation. Following intravenous heparin administration, the acute confusional state and left-sided paresis improved. Case 2: A 40-year-old man was admitted to the hospital with an akinetic mutism preceded by an episode of major depression of a few weeks' duration and deep venous thrombosis of the left leg. Brain MRI revealed bilateral hemorrhagic venous infarcts at the level of globus pallidus. Factor V leiden mutation was found and intravenous heparin treatment was begun without major clinical improvement. Conclusion: Bilateral thalamic or basal ganglia infarcts are rarely seen and cerebral venous thrombosis should be considered in the differential diagnosis of such lesions.
Keywords: Thalamus; globus pallidus; venous infarct; diarrhea; Factor V Leiden mutation; Protein C deficiency; THALAMIC INFARCTION